2021
DOI: 10.1155/2021/6858809
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling Identified Serum Metabolite Biomarkers and Related Metabolic Pathways of Colorectal Cancer

Abstract: Background. The screening and early detection of colorectal cancer (CRC) still remain a challenge due to the lack of reliable and effective serum biomarkers. Thus, this study is aimed at identifying serum biomarkers of CRC that could be used to distinguish CRC from healthy controls. Methods. A prospective 1 : 2 individual matching case-control study was performed which included 50 healthy control subjects and 98 CRC patients. Untargeted metabolomic profiling was conducted with liquid chromatography tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…To increase the sensitivity and specificity in predicting colorectal cancer and improve the understanding of the pathological mechanism of colorectal cancer development, efforts have been made to discover protein and metabolite biomarkers. Recent studies have reported that potential metabolite biomarkers show dysregulated levels in the blood of colorectal cancer patients compared with healthy controls. , However, most of these studies only focus on identifying biomarkers between colorectal cancer and healthy controls . One of the studies grouped the patients based on the risk of colorectal cancer precursors (including conventional adenomas and serrated polyps) and found that lipid metabolism and metabolites may be involved in the early stage of serrated pathway-related colorectal carcinogenesis .…”
Section: Resultsmentioning
confidence: 99%
“…To increase the sensitivity and specificity in predicting colorectal cancer and improve the understanding of the pathological mechanism of colorectal cancer development, efforts have been made to discover protein and metabolite biomarkers. Recent studies have reported that potential metabolite biomarkers show dysregulated levels in the blood of colorectal cancer patients compared with healthy controls. , However, most of these studies only focus on identifying biomarkers between colorectal cancer and healthy controls . One of the studies grouped the patients based on the risk of colorectal cancer precursors (including conventional adenomas and serrated polyps) and found that lipid metabolism and metabolites may be involved in the early stage of serrated pathway-related colorectal carcinogenesis .…”
Section: Resultsmentioning
confidence: 99%
“…COAD is a common cause of cancer-related death worldwide, and some studies have constructed prognostic models for immune-related genes ( 30 ). And through the metabolomics analysis of determining the serum metabolite biomarkers and related metabolic pathways in COAD ( 31 ), which helps to improve the prognostic outcomes of COAD patients. Therefore, a comprehensive comprehensive analysis of immune and metabolic gene characteristics in COAD may help us to further explore the methods and pathways to improve the prognosis of COAD patients and improve the effectiveness of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 12,13-DHOME comes from the oxidation of linoleic acid, which is related to an increased risk of ovarian cancer, cytochrome P450 monooxygenase oxidizes linoleic acid to produce 12,13-DHOME, the role of DHOME in multiple cellular functions may lead to an increased risk of ovarian cancer ( Hada et al, 2019 ). 12-Hydroxydodecanoic acid is one of the biomarkers of serum metabolites of colorectal cancer ( Zhang et al, 2021 ). Indole-3 acetaldehyde is a precursor molecule for tryptophan to form endogenous 6-formylindolo [3,2-b] carbazole (ficz), tryptophan is related to tumor immune escape ( Rannug, 2022 ).…”
Section: Discussionmentioning
confidence: 99%